Stock Prices in the Banking Sector on the Indonesia Stock Exchange: The Role of Profitability, Liquidity, and Solvency Ratios, 2020–2025 - Dinda Ayu Sabrina; Dian Prawitasari; Amalia Nur Chasanah; Almira Santi Samasta (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the effects of profitability, liquidity, and solvency on the stock prices of banking companies listed on the Indonesia Stock Exchange during 2020–2025. It tests whether Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR) significantly influence banking stock prices. Research Method: A quantitative associative design with multiple linear regression was employed. Annual financial statements and stock-price data were collected from 31 banks selected through purposive sampling, producing 186 observations after extreme values were removed using the z-score criterion. Stock prices were transformed into natural logarithms, while ROA, LDR, and CAR remained in ratio form. The data were analyzed using SPSS 26. Results and Discussion: ROA positively and significantly affects stock prices (B = 76.973; p = 0.000), indicating that investors value efficient asset utilization. LDR has no significant effect (B = 0.065; p = 0.847), whereas CAR has a significant negative effect (B = −2.324; p = 0.000), suggesting that excessive capital may indicate inefficient capital utilization. The model explains 37.9% of stock-price variation. Implications: Bank management should strengthen profitability and utilize capital efficiently. Future studies should apply robust panel-data methods and include macroeconomic and bank-specific variables. Originality: This study provides post-pandemic evidence that banking solvency may be interpreted negatively when capital accumulation is not accompanied by productive expansion.